2014
DOI: 10.1016/j.ygyno.2013.10.025
|View full text |Cite
|
Sign up to set email alerts
|

The role and timing of palliative medicine consultation for women with gynecologic malignancies: Association with end of life interventions and direct hospital costs

Abstract: Objective Aggressive care interventions at the end of life (ACE) are reported metrics of sub-optimal quality of end of life care that are modifiable by palliative medicine consultation. Our objective was to evaluate the association of inpatient palliative medicine consultation with ACE scores and direct inpatient hospital costs of patients with gynecologic malignancies. Methods A retrospective review of medical records of the past 100 consecutive patients who died from their primary gynecologic malignancies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 25 publications
4
56
0
Order By: Relevance
“…Our data suggest that patient with high symptom burden may be an appropriate group to consider for standardized palliative care consultation. Our data also add to the growing body of literature supporting the benefits of early integration of palliative care, both earlier rather than later in the disease course [32,[38][39][40] and earlier rather than later in the course of hospitalizations [41][42]. In our cohort, 72% of palliative care consultations happened the day of or the day after admission.…”
Section: Discussionsupporting
confidence: 62%
“…Our data suggest that patient with high symptom burden may be an appropriate group to consider for standardized palliative care consultation. Our data also add to the growing body of literature supporting the benefits of early integration of palliative care, both earlier rather than later in the disease course [32,[38][39][40] and earlier rather than later in the course of hospitalizations [41][42]. In our cohort, 72% of palliative care consultations happened the day of or the day after admission.…”
Section: Discussionsupporting
confidence: 62%
“…In a multivariate analysis involving age, staging, tumor type and race, receiving PC in a timely manner was the only significant predictor of fewer invasive measures at the end of life. Besides, those who were consulted by palliative care staff ≥30 days before death received less invasive measures at the end of life and were associated with lower direct hospital costs [31].…”
Section: Discussionmentioning
confidence: 99%
“…1 This population of seriously ill older adults receives treatment at the end of life that is often of high intensity, 2-4 but has not been clearly linked to higher quality. [3][4][5][6][7][8] Studies have shown that palliative care is associated with increased quality and decreased treatment intensity at the end of life, [9][10][11] specifically demonstrating reduced intensive care unit (ICU) utilization [12][13][14][15][16][17] and increased hospice utilization. [18][19][20] Most hospitals with more than 50 beds have a palliative care program, yet much variation by state and hospital type remains.…”
Section: Introductionmentioning
confidence: 99%